Peningkatan Kualitas Pendidikan Melalui Desentralisasi Pendidikan - Toifur Toifur (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2018)
Abstract: Along with the passing of decentralization of education, it is the impact of government decentralization as a form of Law Number 22 of 1999. Decentralization of education is not just deconcentralization of the central government power delivered to the autonomous regions, but the decentralization of education regarding the very basic problem, namely education belongs to the people and for the people, the process of developing social capital and intellectual capacity of a nation. In this case, the development of education sector in each autonomous region to be conducted. This means that, given the will to organize, empower, reforming the learning process and develop a local curriculum in accordance with the needs and characteristics of the local area. Success or failure of autonomy or the decentralization of education in the era of regional autonomy is determined by three factors which strongly support, namely, the central government, local governments, and schools. Each of these factors has different roles. Yet the differences are owned does not mean nothing related to each other, even the differences are a job distribution, which are mutually support and sustain a successful application in the concept of autonomy and decentralization of education. It may therefore be understood that decentralization provides an opportunity and vast opportunities for each educational unit to improve the quality of education. Keywords: Decentralization, Education Quality, the Education Unit.